Istota systemu zarządzania przedsiębiorstwem w literaturze - Witczak Hubert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Scientific cognitive knowledge of a corporate management system is an important source of normative knowledge in the field. It is expected that the standard, scientific level, and added value of scientific cognition will be of top quality. Research on the status of scientific cognitive knowledge of the corporate management system's essence does not prove meeting the requirement. We face both insufficient scientific cognitive grounds, and unsatisfactory insight into the corporate management system's essence. Thus, there is a need for reviving the dedicated research studies that peaked between the 1970s and 1990s. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 38-47